Nucleofection-based screening of chimeric antigen receptor candidates in human natural killer cells - Wang, Chelsia Qiuxia; Leong, Leonard; Yang, Lei; Xu, Shengli; Lam, Kong-Peng; Choo, Andre Boon-Hwa; Tan, Andy Hee-Meng (Frontiers in Immunology, 2025)
Chimeric antigen receptor (CAR)-modified cell therapy products approved for clinical treatment of hematological malignancies have hitherto been based on T cells. NK cells represent a promising immune cell type that can be considered for CAR engineering due to their potential to be generated as off-the-shelf allogeneic cellular therapy. Viral transduction of NK cells with CARs has been fraught with challenges of long process time and poor CAR transduction efficiency. Here, we describe the development of an optimized protocol for electroporation-based delivery of CAR mRNA into NK cells expanded from human peripheral blood mononuclear cells in the presence of co-stimulating feeder cells. This enabled rapid assessment of the functional capacity of NK cells transiently expressing various CARs to kill liquid and solid tumor cells in vitro. Ultimately, we anticipate that such an approach will enable selection of CAR candidates for their subsequent clinical applicability and manufacturability.